2019
DOI: 10.1038/s41598-018-36473-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of single or combined topical neuroprotective and regenerative agents on degeneration of retinal ganglion cells in rat optic nerve crush model

Abstract: To determine the effectiveness of a single or a combination of topical neurotrophic factors (NFs) in protecting retinal ganglion cells (RGCs) in the rat optic nerve crush (ONC) model, the left ONC was performed to induce the death of the RGCs in adult Sprague-Dawley rats. The NFs studied were tauroursodeoxycholic acid (TUDCA), citicoline, neurotrophin-4 (NT-4), combined TUDCA/citicoline (Doublet-1), combined TUDCA/NT-4 (Doublet-2), combined TUDCA/citicoline/NT-4 (Triplet), and PBS. After 2 weeks, the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…The above-mentioned preventative effects of Citicoline (administered by eye drops) were hypothesized on the basis of reduced neuroretinal structural abnormalities. [84] Similarly, in the optic nerve crush model, with respect to PBS-treated eyes, rats treated with Citicoline combined with tauroursodeoxycholic acid and neurotrophin-4 showed a higher density of RCGs and higher number of RGCs axons [85].…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned preventative effects of Citicoline (administered by eye drops) were hypothesized on the basis of reduced neuroretinal structural abnormalities. [84] Similarly, in the optic nerve crush model, with respect to PBS-treated eyes, rats treated with Citicoline combined with tauroursodeoxycholic acid and neurotrophin-4 showed a higher density of RCGs and higher number of RGCs axons [85].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, dual injection of neural stem cells releasing GDNF or CNTF showed a synergistic effect after ONI [134]. A very recent study of Kitamura et al [135] compared the in vivo effects of single and combined NTF administration on RGC survival in adult rats after ONI. Once more, they showed that the combinatorial approach was the most effective one.…”
Section: Ntfs As Neuroprotective Therapy In Glaucoma: What Informamentioning
confidence: 99%
“…Once more, they showed that the combinatorial approach was the most effective one. Of note, besides NT-4, they studied rather unconventional NTFs: tauroursodeoxycholic acid and citicoline [135]. In sharp contrast, using a laser-induced glaucoma model, Pease et al [136] were unable to show an additive effect of dual injection of viral vectors overexpressing BDNF or CNTF on RGC survival.…”
Section: Ntfs As Neuroprotective Therapy In Glaucoma: What Informamentioning
confidence: 99%
See 1 more Smart Citation
“…TUDCA treatment ameliorates photoreceptor death in naturally occurring, knockout, and transgenic rodent models of retinal diseases [ 3 , 7 , 8 , 9 , 10 , 11 ]. TUDCA also shows the protection of ganglion cells from n -methyl- d -aspartate-induced retinal damage in rats [ 12 ] and a rat model involving crushed optic nerve [ 13 ]. Recently, we have examined the protective effect of TUDCA against photoreceptor degeneration in a retinitis pigmentosa GTPase regulator ( Rpgr ) knockout mouse model of retinitis pigmentosa.…”
Section: Introductionmentioning
confidence: 99%